2017
DOI: 10.1002/aenm.201700770
|View full text |Cite
|
Sign up to set email alerts
|

Burn‐in Free Nonfullerene‐Based Organic Solar Cells

Abstract: Organic solar cells that are free of burn‐in, the commonly observed rapid performance loss under light, are presented. The solar cells are based on poly(3‐hexylthiophene) (P3HT) with varying molecular weights and a nonfullerene acceptor (rhodanine‐benzothiadiazole‐coupled indacenodithiophene, IDTBR) and are fabricated in air. P3HT:IDTBR solar cells light‐soaked over the course of 2000 h lose about 5% of power conversion efficiency (PCE), in stark contrast to [6,6]‐Phenyl C61 butyric acid methyl ester (PCBM)‐ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
217
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 216 publications
(227 citation statements)
references
References 45 publications
9
217
1
Order By: Relevance
“…An inability to tune the chemical structure inhibits morphological or energetic optimization, to the effect that progress in the field has mostly been driven by the design Nonfullerene acceptors (NFAs) dominate organic photovoltaic (OPV) research due to their promising efficiencies and stabilities. [14,15] Accompanied by reports of good compatibility with nonchlorinated solvents [16] and low thickness-dependent performance, [17] NFAs provide encouraging potential for commercial scale-up. Here, the important role of molecular structure and conformation in NFA photostability in air is investigated by comparing structurally similar but conformationally different promising NFAs: planar O-IDTBR and nonplanar O-IDFBR.…”
Section: Introductionmentioning
confidence: 99%
“…An inability to tune the chemical structure inhibits morphological or energetic optimization, to the effect that progress in the field has mostly been driven by the design Nonfullerene acceptors (NFAs) dominate organic photovoltaic (OPV) research due to their promising efficiencies and stabilities. [14,15] Accompanied by reports of good compatibility with nonchlorinated solvents [16] and low thickness-dependent performance, [17] NFAs provide encouraging potential for commercial scale-up. Here, the important role of molecular structure and conformation in NFA photostability in air is investigated by comparing structurally similar but conformationally different promising NFAs: planar O-IDTBR and nonplanar O-IDFBR.…”
Section: Introductionmentioning
confidence: 99%
“…[51,52] Moreover, the instability of morphology would also result from the crystallization of small molecule acceptor (SMA) in the blend film. [5] For instance, Durrant group [56] and Brabec group [57] reported burn-in free nonfullerene solar cells. [17,53,54] This nucleation would enhance growth of crystals due to the extra chemical potential of the SMA crystals, thus forming large crystals over time by depleting the mixed domains.…”
mentioning
confidence: 99%
“…[14] Importantly, nonfullerene-based OSCs have demonstrated a significantly improved light-soaking and thermal stability. [15][16][17] And Kim et al found that the all-polymer photoactive layer with polymer donor and polymer acceptor demonstrated dramatically enhanced flexibility compared with the polymer/PCBM devices, which indicates that all-polymer materials are more suitable as the photoactive layer for the flexible OSCs. [18] Therefore, it is very important to further develop high efficiency donor and acceptor materials with ideal morphology, high flexibility and stability for the development of flexible OSCs.…”
Section: Introductionmentioning
confidence: 99%